Conductive particle
By using conductive particles of specific structures, the problems of fine metal terminal processing difficulties and connection defects in the prior art are solved, and more efficient information processing speed and more stable connections are achieved.
Patent Information
- Application Number
- JP2024229455
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-07-30
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-07-30
AI Technical Summary
The prior art is difficult to deal with subtle metal pins, which leads to prone to connection defects and insufficient information processing speed when connecting the CPU.
Conductive particles with specific structures are used, which are composed of substrate particles and surface conductive parts. The thickness and material selection of the conductive parts can effectively suppress cracks in the conductive parts during repeated compression, ensuring electrical conductivity and mechanical strength.
By using these conductive particles, the occurrence of connection defects can be effectively reduced, the tighter arrangement and narrower spacing can be adapted to the CPU's information processing speed.
Smart Images

Figure 2025060851000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive particle having a conductive portion disposed on the surface of a base particle. The present invention also relates to a connection structure using the conductive particle. [Background technology]
[0002] In recent years, the expansion of markets for IoT, 5G communications, VR, AR, artificial intelligence, and autonomous driving systems has led to an increase in the amount of information and faster communication speeds, which has created an increasing demand for faster information processing speeds in processors for data servers, PCs, mobile devices, and other devices.
[0003] One method for processing large volumes of information at high speed is, for example, improving the processing power of a CPU (Central Processing Unit). In order to improve the processing power of a CPU, the number of pins and the pitch of metal terminals (metal pins) of sockets (CPU sockets) that connect a CPU to a motherboard are increasing.
[0004] An example of a socket using a metal terminal (metal pin) is disclosed in the following Patent Document 1. The following Patent Document 1 discloses an electronic component socket that is interposed between an electronic component such as a semiconductor element or a semiconductor device and a mounting board to detachably mount the electronic component and electrically connect the electronic component and the mounting board. In the electronic component socket, a connection terminal is provided on the mounting surface side of a socket body made of resin. This connection terminal is formed by coating a conductive film on the outer surface of a resin bump that is integral with the socket body and protrudes from the socket body. In the electronic component socket, a connection terminal is provided with a base end joined to the inner surface of the conductive film and a base end side embedded and sealed in the resin bump and the socket body. The tip side of this connection terminal is formed to extend in a bent shape from the surface side opposite to the mounting surface of the socket body. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-297507 A Summary of the Invention [Problem to be solved by the invention]
[0006] 5 is a front cross-sectional view showing a schematic diagram of a connection structure using a metal terminal. The connection structure 101 includes a first connection target member 52, a second connection target member 53, and a connection portion 104. The first connection target member 52 has a plurality of first electrodes 52a on its surface (upper surface). The second connection target member 53 has a plurality of second electrodes 53a on its surface (lower surface). The connection portion 54 has an insulating member 31, a metal terminal (metal pin) 35, and a solder ball 34. The connection portion 104 is a socket portion formed by a socket. The first connection target member 52 is, for example, a motherboard, and the second connection target member 53 is, for example, a CPU.
[0007] In conventional sockets, etc., it is extremely difficult to process fine metal terminals (metal pins) to accommodate the increasing number of pins and narrower pitches. Furthermore, miniaturizing metal terminals (metal pins) reduces their strength, which can lead to metal terminals (metal pins) breaking or bending when connecting to a CPU, etc., resulting in connection failures.
[0008] With conventional sockets that use metal terminals (metal pins), it is difficult to accommodate an increased number of pins and a narrower pitch, making it difficult to achieve faster information processing speeds.
[0009] An object of the present invention is to provide a conductive particle capable of effectively suppressing the occurrence of connection failure. Another object of the present invention is to provide a connection structure using the conductive particle. [Means for solving the problem]
[0010] As a result of extensive investigation into the above problems, the present inventors have found that the above problems can be solved by using specific conductive particles instead of metal terminals (metal pins).
[0011] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle and a conductive portion arranged on a surface of the base particle, the conductive particle having a particle diameter of 30 μm or more, and a ratio of a resistance value of the conductive particle after 20 times of loading and unloading until the conductive particle is compressed by 20% to a resistance value of the conductive particle after one time of loading and unloading until the conductive particle is compressed by 20% is 1.5 or less.
[0012] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle and a conductive portion disposed on a surface of the base particle, the conductive particle having a particle diameter of 30 μm or more, and no bend in a compression displacement-compression load curve in a compression test in which loading and unloading are repeated 20 times until the conductive particle is compressed and deformed by 20%.
[0013] In a specific aspect of the conductive particle according to the present invention, there is no bend in the compression displacement-compression load curve in a compression test in which the conductive particle is subjected to 20 cycles of loading and unloading until it is compressed by 30%.
[0014] According to a broad aspect of the present invention, there is provided a conductive particle comprising a base particle and a conductive portion disposed on a surface of the base particle, the conductive particle having a particle diameter of 30 μm or more, the conductive particle being used to obtain a socket or connector.
[0015] In a specific aspect of the conductive particle according to the present invention, a material of the conductive portion includes a ductile metal.
[0016] In a specific aspect of the conductive particle according to the present invention, the conductive portion has a laminated structure of two or more layers, and a layer other than the outer surface of the conductive portion includes a layer containing a ductile metal.
[0017] In a specific aspect of the conductive particle according to the present invention, the material of the outer surface of the conductive portion is gold, silver, copper, tin, zinc, nickel, beryllium, cobalt, palladium, platinum, rhodium, ruthenium, iridium, or an alloy thereof.
[0018] In a specific aspect of the conductive particle according to the present invention, the layer containing the ductile metal has a thickness of 0.6 μm or more.
[0019] In a specific aspect of the conductive particle according to the present invention, the conductive portion has a thickness of 0.3 μm or more and 20 μm or less.
[0020] In a specific aspect of the conductive particle according to the present invention, the conductive portion has a thickness of 0.6 μm or more and 20 μm or less.
[0021] In a specific aspect of the conductive particle according to the present invention, a ratio of a particle diameter of the conductive particle to a thickness of the conductive portion is 5 or more and 300 or less.
[0022] In a specific aspect of the conductive particle according to the present invention, the conductive particle has a plurality of protrusions on an outer surface of the conductive portion.
[0023] In a specific aspect of the conductive particle according to the present invention, a load necessary for compressing and deforming the conductive particle by 20% is 50 N or less.
[0024] In a specific aspect of the conductive particle according to the present invention, a load necessary for compressing and deforming the conductive particle by 30% is 100 N or less.
[0025] According to a broad aspect of the present invention, there is provided a connection structure comprising a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection portion having an insulating member and conductive particles, wherein the conductive particles are the conductive particles described above, and the first electrode and the second electrode are electrically connected by the conductive particles. Effect of the Invention
[0026] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the particle diameter of the conductive particle is 30 μm or more. In the conductive particle according to the present invention, the ratio of the resistance value of the conductive particle after repeatedly loading and unloading the conductive particle until the conductive particle is compressed by 20% 20 times to the resistance value of the conductive particle after repeatedly loading and unloading the conductive particle until the conductive particle is compressed by 20% once is 1.5 or less. Since the conductive particle according to the present invention has the above configuration, it is possible to effectively suppress the occurrence of poor connection.
[0027] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the particle diameter of the conductive particle is 30 μm or more. In the conductive particle according to the present invention, no bend exists in the compression displacement-compression load curve in a compression test in which the conductive particle is subjected to loading and unloading 20 times until it is compressed and deformed by 20%. Since the conductive particle according to the present invention has the above configuration, it is possible to effectively suppress the occurrence of poor connection.
[0028] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the particle diameter of the conductive particle is 30 μm or more. The conductive particle according to the present invention is used to obtain a socket or connector. Since the conductive particle according to the present invention has the above configuration, the occurrence of poor connection can be effectively suppressed. [Brief description of the drawings]
[0029] [Figure 1] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention. [Diagram 3] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention. [Figure 4] FIG. 4 is a front cross-sectional view that typically shows a connection structure using conductive particles according to the first embodiment of the present invention. [Diagram 5] FIG. 5 is a front cross-sectional view that typically shows a connection structure using a metal terminal. [Figure 6] FIG. 6 is a schematic diagram for explaining the presence or absence of bends in a two-dimensional graph showing a compression displacement (X-axis)-compression load (Y-axis) curve in a compression test of a conductive particle according to one embodiment of the present invention. [Figure 7] FIG. 7 is a schematic diagram for explaining the presence or absence of bends in a two-dimensional graph showing a compression displacement (X-axis)-compression load (Y-axis) curve in a compression test of a conductive particle according to one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0030] The present invention will be described in detail below.
[0031] (Conductive particles) The conductive particle according to the present invention includes a base particle and a conductive portion disposed on a surface of the base particle. In the conductive particle according to the present invention, the particle diameter of the conductive particle is 30 μm or more. In the conductive particle according to the present invention, the ratio of the resistance value of the conductive particle after repeatedly loading and unloading the conductive particle until the conductive particle is compressed by 20% 20 times to the resistance value of the conductive particle after repeatedly loading and unloading the conductive particle until the conductive particle is compressed by 20% once is 1.5 or less.
[0032] The conductive particle according to the present invention includes a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the conductive particle has a particle diameter of 30 μm or more. In the conductive particle according to the present invention, no bend exists in a compression displacement-compression load curve in a compression test in which the conductive particle is subjected to loading and unloading 20 times until the conductive particle is compressed and deformed by 20%.
[0033] The conductive particle according to the present invention comprises a base particle and a conductive portion disposed on the surface of the base particle. In the conductive particle according to the present invention, the conductive particle has a particle diameter of 30 μm or more. The conductive particle according to the present invention is used to obtain a socket or connector. The conductive particle according to the present invention is a conductive particle that can be used to obtain a socket or connector.
[0034] Since each of the conductive particles according to the present invention has the above-mentioned configurations, the occurrence of poor connection can be effectively suppressed.
[0035] In recent years, the expansion of markets for IoT, 5G communications, VR, AR, artificial intelligence, and autonomous driving systems has led to an increase in the amount of information and faster communication speeds, which has created an increasing demand for faster information processing speeds in processors for data servers, PCs, mobile devices, and other devices.
[0036] One method for processing large volumes of information at high speed is, for example, improving the processing power of a CPU (Central Processing Unit). In order to improve the processing power of a CPU, the number of pins and the pitch of metal terminals (metal pins) of sockets (CPU sockets) that connect a CPU to a motherboard are increasing.
[0037] In conventional sockets, etc., it is extremely difficult to process fine metal terminals (metal pins) to accommodate the increasing number of pins and narrower pitches. Furthermore, miniaturizing metal terminals (metal pins) reduces their strength, which can lead to metal terminals (metal pins) breaking or bending when connecting to a CPU, etc., resulting in connection failures.
[0038] With conventional sockets that use metal terminals (metal pins), it is difficult to accommodate an increased number of pins and a narrower pitch, making it difficult to achieve faster information processing speeds.
[0039] As a result of intensively studying the above problems, the present inventors have found that the above problems can be solved by using specific conductive particles instead of metal terminals (metal pins). The conductive particles according to the present invention can effectively suppress the occurrence of cracks in the conductive part even when repeatedly compressed. Therefore, they can be used in place of metal terminals (metal pins) and can accommodate further narrowing of the pitch. As a result, they can accommodate the increase in the information processing speed of CPUs and the like.
[0040] Furthermore, since each of the conductive particles according to the present invention has the above-mentioned configurations, the conductive portion is less likely to crack even when repeatedly compressed, and therefore the occurrence of poor connections when connecting a CPU, etc. can be effectively suppressed.
[0041] In the present invention, the use of specific conductive particles greatly contributes to obtaining the above-mentioned effects.
[0042] In the conductive particles, the ratio (R20 / R1) of the resistance value (R20) of the conductive particles after 20 times of loading and unloading until the conductive particles are compressed and deformed by 20% to the resistance value (R1) of the conductive particles after one time of loading and unloading until the conductive particles are compressed and deformed by 20% satisfies the following range. That is, the ratio (R20 / R1) is preferably 0.5 or more, more preferably 0.8 or more, and preferably 1.5 or less, more preferably 1.3 or less. When the ratio (R20 / R1) is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of poor connection can be more effectively suppressed.
[0043] The resistance value (R1) and the resistance value (R20) can be measured as follows.
[0044] Using a micro-compression tester, a load is applied to the conductive particles in the center direction of the conductive particles at 25°C with the smooth indenter end face of a cylinder (diameter 500 μm, made of BeCu / Au on stainless steel) until the conductive particles are compressed by 20%. The process of unloading is counted as one cycle, and a total of 20 cycles of compression tests are performed. After 20% compression deformation in the first cycle, the conductive resistance is measured in the 20% compressed state and this is defined as the resistance value (R1). Similarly, after 20% compression deformation in the 20th cycle, the conductive resistance is measured in the 20% compressed state and this is defined as the resistance value (R20). As the micro-compression tester, an "ENT-NEXUS" manufactured by Elionix, a "Micro Autograph MST-I" manufactured by Shimadzu Corporation, or the like is used.
[0045] The conductive particles preferably have no bends in a compression displacement-compression load curve in a compression test in which the conductive particles are repeatedly loaded and unloaded 20 times until the conductive particles are compressed by 20%.The conductive particles preferably have no bends in a compression displacement-compression load curve (compression displacement curve) in a compression test in which the conductive particles are repeatedly loaded and unloaded 20 times until the conductive particles are compressed by 30%.
[0046] In the present invention, "no bends" means that no sudden displacement occurs in the compression displacement curve in a two-dimensional graph showing the relationship between the compression displacement (X-axis) and the compression load (Y-axis) during a compression test in which loading and unloading are repeated 20 times until 20% or 30% compression is achieved at a loading rate of 0.3 mN / sec. For example, the results of a compression test in which loading and unloading are repeated once until 20% compression are achieved are shown in FIG. 6. FIG. 6 shows a two-dimensional graph in which no bends exist during the compression test. Note that FIG. 6 shows the results of a compression test in which loading and unloading are repeated once until 20% compression is achieved, and in the present invention, even in a compression test in which loading and unloading are repeated 20 times until 20% compression is achieved, no bends exist during the compression test.
[0047] In addition, in the present invention, "there is a bent part" means that a sudden displacement occurs in the compression displacement curve in a two-dimensional graph showing the relationship between the compression displacement (X-axis) and the compression load (Y-axis) during a compression test in which loading and unloading are repeated 20 times until the compression is 20% or 30% at a loading rate of 0.3 mN / sec. The sudden displacement of the compression displacement curve occurs, for example, when a large crack having a length of 50% or more of the particle diameter occurs along the surface of the conductive particle. For example, the result of a compression test in which loading and unloading are repeated once until the compression is 20% is shown in FIG. 7. FIG. 7 shows a two-dimensional graph in which a bent part exists during the compression test.
[0048] Specifically, the presence or absence of the bent portion can be confirmed as follows.
[0049] Using a micro-compression tester, a load is applied to the conductive particles in the center direction at 25°C with a smooth indenter end face of a cylinder (diameter 500 μm, made of diamond) under conditions of a compression speed of 0.3 mN / sec until the conductive particles are compressed by 20% or 30% and then unloaded, and a total of 20 cycles of compression tests are performed. The compression displacement (μm) and compression load (mN) during this period are measured, and the presence or absence of a bend in the compression displacement curve showing the relationship between the compression displacement (X-axis) and the compression load (Y-axis) is confirmed. As the above-mentioned micro-compression tester, the "ENT-NEXUS" manufactured by Elionix, the "Micro Autograph MST-I" manufactured by Shimadzu Corporation, etc. are used.
[0050] From the viewpoint of more effectively suppressing the occurrence of connection defects, the load required for compressing and deforming the conductive particles by 20% is preferably 50 N or less.
[0051] From the viewpoint of more effectively suppressing the occurrence of poor connection, the load necessary to compress and deform the conductive particles by 30% is preferably 100 N or less.
[0052] The particle diameter of the conductive particles is 30 μm or more. The particle diameter of the conductive particles is preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and preferably 2000 μm or less, more preferably 1000 μm or less, even more preferably 600 μm or less. When the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, it can be used more suitably to obtain a socket or a connector. When the particle diameter of the conductive particles is the above lower limit or more and the above upper limit or less, the contact area between the conductive particles and the electrode can be sufficiently large, and when forming the conductive part, the conductive particles are less likely to be aggregated, and the conductive part is less likely to peel off from the surface of the base particle.
[0053] The particle diameter of the conductive particles is preferably an average particle diameter, and is preferably a number average particle diameter. The particle diameter of the conductive particles is, for example, obtained by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average particle diameter of each conductive particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or an optical microscope, the particle diameter of each conductive particle is obtained as a particle diameter of a circle equivalent diameter. In the observation with an electron microscope or an optical microscope, the average particle diameter of 50 arbitrary conductive particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each conductive particle is obtained as a particle diameter of a sphere equivalent diameter. The average particle diameter of the conductive particles is preferably calculated using a particle size distribution measuring device.
[0054] The conductive particles preferably have a particle size variation coefficient (CV value) of 10% or less, more preferably 5% or less. When the conductive particles have a particle size variation coefficient of the upper limit or less, the contact area between the conductive particles and the electrode can be sufficiently large.
[0055] The coefficient of variation (CV value) can be measured as follows.
[0056] CV value (%) = (ρ / Dn) × 100 ρ: Standard deviation of the particle size of the conductive particles Dn: Average particle size of conductive particles
[0057] The shape of the conductive particles is not particularly limited. The conductive particles may be spherical or may have a shape other than spherical, such as a square pillar, a cylinder, or a flat shape.
[0058] The present invention will now be described in detail with reference to the drawings.
[0059] FIG. 1 is a cross-sectional view showing a conductive particle according to a first embodiment of the present invention.
[0060] The conductive particle 1 shown in Fig. 1 has a base particle 2 and a conductive portion 3. The conductive portion 3 is disposed on the surface of the base particle 2. In the first embodiment, the conductive portion 3 is in contact with the surface of the base particle 2. The conductive particle 1 is a coated particle in which the surface of the base particle 2 is coated with the conductive portion 3.
[0061] In the conductive particle 1, the conductive portion 3 is a single-layer conductive layer. In the conductive particle 1, the base particle 2 contains a conductive metal inside the base particle 2. In the conductive particle, the conductive portion may cover the entire surface of the base particle, or the conductive portion may cover a part of the surface of the base particle. In the conductive particle, the conductive portion may be a single-layer conductive layer, or may be a multi-layer conductive layer composed of two or more layers.
[0062] Unlike conductive particles 11 and 21 described below, conductive particle 1 does not have a core substance. Conductive particle 1 does not have protrusions on its surface. Conductive particle 1 is spherical. Conductive portion 3 does not have protrusions on its outer surface. In this way, the conductive particle according to the present invention may not have protrusions on its conductive surface and may be spherical.
[0063] FIG. 2 is a cross-sectional view showing a conductive particle according to a second embodiment of the present invention.
[0064] 2 includes a base particle 2, a conductive portion 12, and a plurality of core materials 13. The conductive portion 12 is disposed on the surface of the base particle 2 so as to be in contact with the base particle 2.
[0065] In the conductive particle 11, the conductive portion 12 is a single-layer conductive layer. In the conductive particle 11, the base particle 2 contains a conductive metal inside the base particle 2. In the conductive particle, the conductive portion may cover the entire surface of the base particle, or the conductive portion may cover a part of the surface of the base particle. In the conductive particle, the conductive portion may be a single-layer conductive layer, or may be a multi-layer conductive layer composed of two or more layers.
[0066] The conductive particle 11 has a plurality of protrusions 11a on its conductive surface. The conductive portion 12 has a plurality of protrusions 12a on its outer surface. A plurality of core substances 13 are disposed on the surface of the base particle 2. The plurality of core substances 13 are embedded in the conductive portion 12. The core substances 13 are disposed inside the protrusions 11a, 12a. The conductive portion 12 covers the plurality of core substances 13. The outer surface of the conductive portion 12 is raised by the plurality of core substances 13, forming the protrusions 11a, 12a.
[0067] FIG. 3 is a cross-sectional view showing a conductive particle according to a third embodiment of the present invention.
[0068] 3 has a base particle 2, a conductive portion 22, and a plurality of core materials 13. The conductive portion 22 as a whole has a first conductive portion 22A on the base particle 2 side and a second conductive portion 22B on the side opposite to the base particle 2 side.
[0069] The only difference between conductive particle 11 and conductive particle 21 is the conductive portion. That is, conductive particle 11 has conductive portion 12 with a single layer structure, whereas conductive particle 21 has first conductive portion 22A and second conductive portion 22B with a two-layer structure. First conductive portion 22A and second conductive portion 22B are formed as separate conductive portions.
[0070] The first conductive portion 22A is disposed on the surface of the base particle 2. The first conductive portion 22A is disposed between the base particle 2 and the second conductive portion 22B. The first conductive portion 22A is in contact with the base particle 2. The second conductive portion 22B is in contact with the first conductive portion 22A. Therefore, the first conductive portion 22A is disposed on the surface of the base particle 2, and the second conductive portion 22B is disposed on the surface of the first conductive portion 22A. The conductive particle 21 has a plurality of protrusions 21a on its conductive surface. The conductive portion 22 has a plurality of protrusions 22a on its outer surface. The first conductive portion 22A has a plurality of protrusions 22Aa on its outer surface. The second conductive portion 22B has a plurality of protrusions 22Ba on its outer surface.
[0071] Other details of the conductive particles will be described below.
[0072] (base material particles) The material of the base particle is not particularly limited. The material of the base particle may be an organic material or an inorganic material. Examples of the base particle formed only from the organic material include resin particles. Examples of the base particle formed only from the inorganic material include inorganic particles other than metals. Examples of the base particle formed from both the organic material and the inorganic material include organic-inorganic hybrid particles. From the viewpoint of further improving the compression characteristics of the base particle, the base particle is preferably a resin particle or an organic-inorganic hybrid particle, and more preferably a resin particle.
[0073] Examples of the organic material include polyolefin resins such as polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyvinylidene chloride, polyisobutylene, and polybutadiene; acrylic resins such as polymethyl methacrylate and polymethyl acrylate; polycarbonate, polyamide, phenol formaldehyde resin, melamine formaldehyde resin, benzoguanamine formaldehyde resin, urea formaldehyde resin, phenol resin, melamine resin, benzoguanamine resin, urea resin, epoxy resin, unsaturated polyester resin, saturated polyester resin, polyethylene terephthalate, polysulfone, polyphenylene oxide, polyacetal, polyimide, polyamideimide, polyether ether ketone, polyether sulfone, divinylbenzene polymer, and divinylbenzene copolymer. Examples of the divinylbenzene copolymer include divinylbenzene-styrene copolymer and divinylbenzene-(meth)acrylic acid ester copolymer. The material of the base particle is preferably a polymer obtained by polymerizing one or more polymerizable monomers having an ethylenically unsaturated group, since the compression characteristics of the base particle can be easily controlled within a suitable range.
[0074] When the base particle is obtained by polymerizing a polymerizable monomer having an ethylenically unsaturated group, the polymerizable monomer having an ethylenically unsaturated group includes a non-crosslinkable monomer and a crosslinkable monomer.
[0075] Examples of the non-crosslinkable monomer include vinyl compounds such as styrene monomers, α-methylstyrene, and chlorostyrene; vinyl ether compounds such as methyl vinyl ether, ethyl vinyl ether, and propyl vinyl ether; acid vinyl ester compounds such as vinyl acetate, vinyl butyrate, vinyl laurate, and vinyl stearate; halogen-containing monomers such as vinyl chloride and vinyl fluoride; and (meth)acrylic compounds such as methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, lauryl (meth)acrylate, cetyl (meth)acrylate, stearyl (meth)acrylate, cyclohexyl Examples of suitable (meth)acrylate compounds include alkyl (meth)acrylate compounds such as (meth)acrylate and isobornyl (meth)acrylate; oxygen-containing (meth)acrylate compounds such as 2-hydroxyethyl (meth)acrylate, glycerol (meth)acrylate, polyoxyethylene (meth)acrylate, and glycidyl (meth)acrylate; nitrile-containing monomers such as (meth)acrylonitrile; halogen-containing (meth)acrylate compounds such as trifluoromethyl (meth)acrylate and pentafluoroethyl (meth)acrylate; α-olefin compounds such as diisobutylene, isobutylene, linearne, ethylene, and propylene; and conjugated diene compounds such as isoprene and butadiene.
[0076] Examples of the crosslinkable monomer include vinyl compounds such as vinyl monomers, e.g., divinylbenzene, 1,4-divinyloxybutane, and divinylsulfone; (meth)acrylic compounds such as polyfunctional (meth)acrylate compounds, e.g., tetramethylolmethane tetra(meth)acrylate, polytetramethylene glycol diacrylate, tetramethylolmethane tri(meth)acrylate, tetramethylolmethane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, dipentaerythritol penta(meth)acrylate, glycerol tri(meth)acrylate, glycerol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, and 1,4-butanediol di(meth)acrylate; and allyl compounds. Examples of the silane compounds include silane alkoxide compounds such as tetramethoxysilane, tetraethoxysilane, methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, isopropyltrimethoxysilane, isobutyltrimethoxysilane, cyclohexyltrimethoxysilane, n-hexyltrimethoxysilane, n-octyltriethoxysilane, n-decyltrimethoxysilane, phenyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, diisopropyldimethoxysilane, trimethoxysilylstyrene, γ-(meth)acryloxypropyltrimethoxysilane, 1,3-divinyltetramethyldisiloxane, methylphenyldimethoxysilane, and diphenyldimethoxysilane;Examples of the silane alkoxides include silanes containing polymerizable double bonds, such as vinyltrimethoxysilane, vinyltriethoxysilane, dimethoxymethylvinylsilane, dimethoxyethylvinylsilane, diethoxymethylvinylsilane, diethoxyethylvinylsilane, ethylmethyldivinylsilane, methylvinyldimethoxysilane, ethylvinyldimethoxysilane, methylvinyldiethoxysilane, ethylvinyldiethoxysilane, p-styryltrimethoxysilane, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, and 3-acryloxypropyltrimethoxysilane; cyclic siloxanes such as decamethylcyclopentasiloxane; modified (reactive) silicone oils such as one-end modified silicone oil, both-end silicone oil, and side-chain silicone oil; and carboxyl group-containing monomers such as (meth)acrylic acid, maleic acid, and maleic anhydride.
[0077] The base particle can be obtained by polymerizing the polymerizable monomer having the ethylenically unsaturated group.The polymerization method is not particularly limited, and includes known methods such as radical polymerization, ionic polymerization, polycondensation (condensation polymerization, condensation polymerization), addition condensation, living polymerization, and living radical polymerization.Another polymerization method includes suspension polymerization in the presence of a radical polymerization initiator.
[0078] Examples of the inorganic material include silica, alumina, barium titanate, zirconia, carbon black, silicate glass, borosilicate glass, lead glass, soda-lime glass, and alumina silicate glass.
[0079] The base particle may be an organic-inorganic hybrid particle. The base particle may be a core-shell particle. When the base particle is an organic-inorganic hybrid particle, examples of the inorganic material of the base particle include silica, alumina, barium titanate, zirconia, and carbon black. The inorganic material is preferably not a metal. The base particle formed of silica is not particularly limited, but examples include base particles obtained by hydrolyzing a silicon compound having two or more hydrolyzable alkoxysilyl groups to form crosslinked polymer particles, and then baking the resulting particles as necessary. The organic-inorganic hybrid particle may be an organic-inorganic hybrid particle formed of a crosslinked alkoxysilyl polymer and an acrylic resin.
[0080] The organic-inorganic hybrid particles are preferably core-shell type organic-inorganic hybrid particles having a core and a shell disposed on the surface of the core. The core is preferably an organic core. The shell is preferably an inorganic shell. The base particle is preferably an organic-inorganic hybrid particle having an organic core and an inorganic shell disposed on the surface of the organic core.
[0081] Examples of the material for the organic core include the organic materials described above.
[0082] The material of the inorganic shell may be any of the inorganic substances listed as the material of the base particle. The material of the inorganic shell is preferably silica. The inorganic shell is preferably formed by forming a shell-like material from a metal alkoxide on the surface of the core by a sol-gel method, and then firing the shell-like material. The metal alkoxide is preferably a silane alkoxide. The inorganic shell is preferably formed from a silane alkoxide.
[0083] The particle diameter of the base particle is preferably 30 μm or more. The particle diameter of the base particle is preferably 100 μm or more, more preferably 200 μm or more, even more preferably 300 μm or more, and preferably 2000 μm or less, more preferably 1000 μm or less, even more preferably 600 μm or less. When the particle diameter of the base particle is the above lower limit or more and the above upper limit or less, it can be used more suitably to obtain a socket or connector. When the particle diameter of the base particle is the above lower limit or more and the above upper limit or less, the contact area between the conductive particle and the electrode can be sufficiently large, and when forming the conductive part, aggregated conductive particles are unlikely to be formed, and the conductive part is unlikely to peel off from the surface of the base particle.
[0084] The particle diameter of the base particle is particularly preferably 30 μm or more and 1000 μm or less. When the particle diameter of the base particle is within the range of 30 μm or more and 1000 μm or less, it is difficult to aggregate when forming a conductive part on the surface of the base particle, and it is difficult to form aggregated conductive particles. In addition, when the particle diameter of the base particle is within the range of 100 μm or more and 800 μm or less, it can be more suitably used to obtain a socket or connector.
[0085] The particle size of the base particle refers to the diameter when the base particle is a perfect sphere, and refers to the diameter when the base particle is not a perfect sphere having a volume equivalent to that of the base particle.
[0086] The particle diameter of the base particle indicates the number average particle diameter. The particle diameter of the base particle is obtained by observing 50 arbitrary base particles with an electron microscope or optical microscope and calculating the average particle diameter of each base particle, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each base particle is obtained as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary base particles with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each base particle is obtained as the particle diameter of a sphere equivalent diameter. The average particle diameter of the base particles is preferably calculated using a particle size distribution measuring device. When the particle diameter of the base particles in the conductive particles is measured, it can be measured, for example, as follows.
[0087] The conductive particles are added to Kulzer's Technovit 4000 so that the content of the conductive particles is 30% by weight, and dispersed to prepare a resin body for embedding conductive particles for inspection. An ion milling device (Hitachi High-Technologies' IM4000) is used to cut out a cross section of the conductive particles so that it passes through the center of the conductive particles dispersed in the resin body for inspection. Then, 50 conductive particles are randomly selected using a field emission scanning electron microscope (FE-SEM), and the base particle of each conductive particle is observed. The particle diameter of the base particle in each conductive particle is measured, and the arithmetic average of the measured particle diameters is determined as the particle diameter of the base particle.
[0088] (Conductive part) The conductive particle according to the present invention includes a base particle and a conductive portion disposed on the surface of the base particle. The conductive portion preferably contains a metal. The metal constituting the conductive portion is not particularly limited.
[0089] Examples of the metal constituting the conductive part and the conductive metal include gold, silver, palladium, copper, platinum, zinc, iron, tin, lead, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, beryllium, rhodium, ruthenium, iridium, bismuth, thallium, germanium, cadmium, silicon, tungsten, molybdenum, and alloys thereof. Examples of the metal constituting the conductive part and the conductive metal include tin-doped indium oxide (ITO) and solder. Only one type of metal may be used as the metal constituting the conductive part, or two or more types may be used in combination.
[0090] From the viewpoint of more effectively lowering the connection resistance, the conductive portion preferably contains nickel, gold, palladium, beryllium, cobalt, tin, silver, or copper, and more preferably contains nickel, gold, or copper.
[0091] From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive part and more effectively suppressing the occurrence of poor connection, it is preferable that the material of the conductive part contains a ductile metal. The ductile metal preferably has ductility. Specifically, the ductile metal preferably has an elongation rate of 5% or more and 65% or less at 23°C, and more preferably has an elongation rate of 10% or more and 60% or less at 23°C. Examples of the ductile metal include gold, copper, zinc, tin, aluminum, titanium, and alloys thereof. Only one type of the ductile metal may be used, or two or more types may be used in combination.
[0092] The elongation of the ductile metal at 23° C. can be measured as follows.
[0093] A ductile metal film having a thickness of 1 μm is formed on one side of a PET film (G2) (manufactured by Teijin DuPont, size 20 mm x 50 mm) using a ductile metal. A tensile test is conducted to measure the elongation at the time when the ductile metal film breaks. The elongation is measured using a tensile tester (Shimadzu Corporation's "EZ-LX HS") at 23°C and a test speed of 1 mm / min. From the obtained results, the elongation percentage is calculated using the following formula.
[0094] Elongation rate (%) = (L1-L0) / L0 x 100 L1: Length of ductile metal film at break L0: Length of the ductile metal film before testing
[0095] The content of the ductile metal in 100% by weight of the metal material of the conductive part is preferably 10% by weight or more, more preferably 20% by weight or more, and even more preferably 40% by weight or more. The upper limit of the content of the ductile metal in 100% by weight of the metal material of the conductive part is not particularly limited. The content of the ductile metal in 100% by weight of the metal material of the conductive part may be 100% by weight (total amount) or less than 100% by weight. When the content of the ductile metal is equal to or more than the lower limit, the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed.
[0096] From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive portion and more effectively suppressing the occurrence of poor connections, the ductile metal preferably contains copper, tin or zinc, more preferably contains copper or tin, and even more preferably contains copper.
[0097] In 100% by weight of the copper-containing conductive part, the copper content is preferably 10% by weight or more, more preferably 20% by weight or more, and even more preferably 40% by weight or more. In 100% by weight of the copper-containing conductive part, the upper limit of the copper content is not particularly limited. In 100% by weight of the copper-containing conductive part, the copper content may be 90% by weight or less. When the copper content is equal to or more than the lower limit, the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed.
[0098] The conductive portion may be formed of one layer. The conductive portion may be formed of multiple layers. The conductive portion may have a two-layer laminate structure, a two or more layer laminate structure, a three-layer laminate structure, or a three or more layer laminate structure. From the viewpoint of more effectively suppressing the occurrence of cracks in the conductive portion and more effectively suppressing the occurrence of connection defects, it is preferable that the conductive portion has a two or more layer laminate structure.
[0099] When the conductive part has a laminated structure of two or more layers, the material other than the outer surface of the conductive part preferably contains a ductile metal, more preferably contains copper, tin, or an alloy thereof. If the material other than the outer surface of the conductive part is the above-mentioned preferred metal (ductile metal), the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of connection failure can be more effectively suppressed.
[0100] When the conductive part has a laminated structure of two or more layers, it is preferable that the conductive part includes a layer containing a ductile metal. When the conductive part has a laminated structure of two or more layers, it is preferable that a layer other than the outer surface of the conductive part includes a layer containing a ductile metal. By having a layer other than the outer surface of the conductive part include a layer containing the ductile metal, it is possible to more effectively suppress the occurrence of cracks in the conductive part and more effectively suppress the occurrence of connection failures. In particular, when the outer surface is not a layer containing the ductile metal, the presence of a layer containing the ductile metal in a layer other than the outer surface can more effectively suppress the occurrence of cracks in the conductive part and more effectively suppress the occurrence of connection failures.
[0101] The content of the ductile metal in 100% by weight of the metal that is the material of the layer containing the ductile metal is preferably 30% by weight or more, more preferably 60% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more. The upper limit of the content of the ductile metal in 100% by weight of the metal that is the material of the layer containing the ductile metal is not particularly limited. The content of the ductile metal in 100% by weight of the metal that is the material of the layer containing the ductile metal may be 100% by weight (total amount) or less than 100% by weight. When the content of the ductile metal is equal to or more than the lower limit, the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed.
[0102] The thickness of the layer containing the ductile metal is preferably 0.6 μm or more, more preferably 1.0 μm or more, even more preferably 2.0 μm or more, and particularly preferably 4.0 μm or more. When the thickness of the layer containing the ductile metal is equal to or more than the lower limit, the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed. The thickness of the layer containing the ductile metal is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. When the thickness of the layer containing the ductile metal is equal to or less than the upper limit, the compressive deformation when a force is applied perpendicularly to the conductive particles is not hindered, and the contact area with the connecting member can be secured, thereby stabilizing the conductive resistance. In addition, when there are multiple layers containing the ductile metal, the above effect can be obtained when the total thickness of the layers containing the ductile metal is equal to or more than the lower limit and equal to or less than the upper limit.
[0103] When the conductive part has a laminated structure of two or more layers, the material of the outer surface of the conductive part is preferably gold, silver, copper, tin, zinc, nickel, beryllium, cobalt, palladium, platinum, rhodium, ruthenium, iridium, or an alloy thereof, and more preferably gold, copper, or an alloy thereof. When the material of the outer surface of the conductive part is the above-mentioned preferred metal, the connection resistance can be more effectively reduced and the corrosion resistance can be more effectively increased.
[0104] The method of forming the conductive portion on the surface of the base particle is not particularly limited. Examples of the method of forming the conductive portion include electroless plating, electroplating, physical collision, mechanochemical reaction, physical vapor deposition or physical adsorption, and a method of coating the surface of the base particle with a metal powder or a paste containing a metal powder and a binder. The method of forming the conductive portion is preferably electroless plating, electroplating, or a physical collision method. Examples of the physical vapor deposition method include vacuum deposition, ion plating, and ion sputtering. Examples of the physical collision method include a sheeter composer (manufactured by Tokuju Kosakusho Co., Ltd.).
[0105] The thickness of the conductive part is preferably 0.3 μm or more, more preferably 0.6 μm or more, and even more preferably 1 μm or more, and is preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. The thickness of the conductive part means the thickness of the entire conductive part when the conductive part has a laminated structure of two or more layers. When the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, the occurrence of cracks in the conductive part can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed. In addition, when the thickness of the conductive part is equal to or more than the lower limit and equal to or less than the upper limit, sufficient conductivity can be obtained and the conductive particles can be prevented from hardening.
[0106] When the conductive part has a laminated structure of two or more layers, the thickness of the conductive part of the outermost layer is preferably 0.001 μm or more, more preferably 0.01 μm or more, and preferably 10 μm or less, more preferably 8 μm or less. When the thickness of the conductive part of the outermost layer is equal to or more than the lower limit and equal to or less than the upper limit, the coating of the conductive part of the outermost layer becomes more uniform, and the corrosion resistance can be more effectively improved. In addition, when the metal constituting the outermost layer is gold, the thinner the thickness of the outermost layer, the lower the cost.
[0107] The thickness of the conductive part can be measured by observing the cross section of the conductive particle using, for example, a transmission electron microscope (TEM). The thickness of the conductive part is preferably calculated as the average value of the thicknesses of five arbitrary conductive parts as the thickness of the conductive part of one conductive particle, and more preferably calculated as the average value of the thickness of the entire conductive part as the thickness of the conductive part of one conductive particle. The thickness of the conductive part is preferably determined by calculating the average thickness of the conductive part of each of 10 arbitrary conductive particles.
[0108] The ratio of the particle diameter of the conductive particles to the thickness of the conductive portion (particle diameter of conductive particles / thickness of conductive portion) is preferably at least 5, more preferably at least 10, and even more preferably at least 20, and is preferably at most 800, more preferably at most 650, and even more preferably at most 300. When the ratio (particle diameter of conductive particles / thickness of conductive portion) is at least the lower limit and at most the upper limit, the occurrence of cracks in the conductive portion can be more effectively suppressed, and the occurrence of poor connection can be more effectively suppressed.
[0109] (core substance) The conductive particles preferably have protrusions on the outer surface of the conductive part. The conductive particles preferably have protrusions on the conductive surface. The protrusions are preferably multiple. An oxide film is often formed on the surface of the electrode that contacts the conductive particles. When conductive particles having protrusions on the surface of the conductive part are used, the oxide film can be effectively removed by the protrusions by pressing the conductive particles and the electrode. Therefore, the electrode and the conductive part are more reliably in contact with each other, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced. Furthermore, when the conductive particles are dispersed in a binder and used as a conductive material, the binder between the conductive particles and the electrode can be more effectively removed by the protrusions of the conductive particles. Therefore, the contact area between the conductive particles and the electrode can be sufficiently increased, and the connection resistance can be more effectively reduced.
[0110] Examples of the method for forming the protrusions include a method in which a core material is attached to the surface of a base particle, and then a conductive portion is formed by electroless plating, and a method in which a conductive portion is formed on the surface of a base particle by electroless plating, and then a core material is attached, and then a conductive portion is formed by electroless plating, etc. Also, the core material does not have to be used to form the protrusions.
[0111] Other methods for forming the protrusions include a method of adding a core substance during the process of forming a conductive portion on the surface of a base particle, etc. Alternatively, to form the protrusions, a method may be used in which, without using the core substance, a conductive portion is formed on the base particle by electroless plating, a plating is deposited in the form of protrusions on the surface of the conductive portion, and the conductive portion is further formed by electroless plating, etc.
[0112] Examples of the method for attaching the core substance to the surface of the base particle include a method of adding the core substance to a dispersion liquid of the base particle, and accumulating and attaching the core substance to the surface of the base particle by van der Waals force, and a method of adding the core substance to a container containing the base particle, and attaching the core substance to the surface of the base particle by mechanical action such as rotating the container, etc. From the viewpoint of controlling the amount of the core substance to be attached, the method for attaching the core substance to the surface of the base particle is preferably a method of accumulating and attaching the core substance to the surface of the base particle in the dispersion liquid.
[0113] The materials constituting the core material include conductive materials and non-conductive materials. The conductive materials include conductive non-metals such as metals, metal oxides, and graphite, and conductive polymers. The conductive polymers include polyacetylene. The non-conductive materials include silica, alumina, titanium oxide, and zirconia. From the viewpoint of more effectively removing the oxide film, it is preferable that the core material is hard. From the viewpoint of more effectively lowering the connection resistance between the electrodes, it is preferable that the core material is a metal.
[0114] The metal is not particularly limited. Examples of the metal include gold, silver, copper, platinum, zinc, iron, lead, tin, aluminum, cobalt, indium, nickel, chromium, titanium, antimony, bismuth, germanium, and cadmium, as well as alloys consisting of two or more metals, such as tin-lead alloy, tin-copper alloy, tin-silver alloy, tin-lead-silver alloy, and tungsten carbide. From the viewpoint of more effectively lowering the connection resistance between the electrodes, the metal is preferably nickel, copper, silver, or gold. The metal may be the same as or different from the metal constituting the conductive portion (conductive layer).
[0115] The shape of the core material is not particularly limited. The core material is preferably in the form of a lump. Examples of the core material include a particulate lump, an aggregate of a plurality of microparticles, and an amorphous lump.
[0116] The particle size of the core material is preferably 0.001 μm or more, more preferably 0.05 μm or more, and preferably 0.9 μm or less, more preferably 0.2 μm or less. When the particle size of the core material is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be more effectively reduced.
[0117] The particle diameter of the core material is preferably an average particle diameter, and more preferably a number average particle diameter. The particle diameter of the core material is determined by observing 50 arbitrary core materials with an electron microscope or optical microscope and calculating the average particle diameter of each core material, or by using a particle size distribution measuring device. In the observation with an electron microscope or optical microscope, the particle diameter of each core material is determined as the particle diameter of a circle equivalent diameter. In the observation with an electron microscope or optical microscope, the average particle diameter of 50 arbitrary core materials with a circle equivalent diameter is almost equal to the average particle diameter of a sphere equivalent diameter. In the particle size distribution measuring device, the particle diameter of each core material is determined as the particle diameter of a sphere equivalent diameter. The average particle diameter of the core material is preferably calculated using a particle size distribution measuring device.
[0118] The number of the protrusions per conductive particle is preferably 3 or more, more preferably 5 or more. The upper limit of the number of the protrusions is not particularly limited. The upper limit of the number of the protrusions can be appropriately selected in consideration of the particle diameter of the conductive particles. When the number of the protrusions is equal to or more than the lower limit, the connection resistance between the electrodes can be more effectively reduced.
[0119] The number of protrusions can be calculated by observing any conductive particle with an electron microscope or an optical microscope. The number of protrusions is preferably determined by observing 50 arbitrary conductive particles with an electron microscope or an optical microscope and calculating the average number of protrusions on each conductive particle.
[0120] The height of the protrusions is preferably 0.001 μm or more, more preferably 0.05 μm or more, and is preferably 0.9 μm or less, more preferably 0.2 μm or less. When the height of the protrusions is equal to or more than the lower limit and equal to or less than the upper limit, the connection resistance between the electrodes can be reduced more effectively.
[0121] The height of the protrusions can be calculated by observing the protrusions of any conductive particle with an electron microscope or an optical microscope. The height of the protrusions is preferably calculated by taking the average value of the heights of all the protrusions per conductive particle as the height of the protrusions of one conductive particle. The height of the protrusions is preferably determined by calculating the average value of the heights of the protrusions of 50 arbitrary conductive particles.
[0122] (Application) The conductive particles are preferably used to obtain a socket or connector. The conductive particles are preferably used to obtain a socket or connector instead of a metal terminal (metal pin). The conductive particles are preferably used for socket or connector applications. The conductive particles are preferably used for socket or connector applications instead of a metal terminal (metal pin). By using the conductive particles instead of a metal terminal (metal pin), it is possible to deal with further narrowing of pitch, and it is possible to effectively suppress the occurrence of connection failures when connecting a CPU. Examples of the socket include a CPU socket, an IC socket, a DIP socket, a PGA socket, a SiP socket, an LGA socket, a CSP socket, a QFN, a QFP socket, a SOP socket, and a BGA socket. Note that the DIP socket, the PGA socket, the SiP socket, the LGA socket, the CSP socket, the QFN, the QFP socket, the SOP socket, and the BGA socket may each be a part of an IC socket. Examples of the connector include an FPC connector, a board-to-board connector, a narrow pitch connector, a DIN connector, a compression connector, a one-piece connector, and a card edge connector.
[0123] (Conductive materials) The conductive particles are preferably dispersed in a binder and used as a conductive material. The conductive material includes the conductive particles and a binder. The conductive particles are preferably dispersed in a binder and used as a conductive material. The conductive material is preferably used for electrical connection between electrodes. Since the conductive material uses the conductive particles described above, the connection resistance between electrodes can be more effectively reduced and the occurrence of aggregation between conductive particles can be more effectively suppressed. Since the conductive material uses the conductive particles described above, the occurrence of connection failure can be more effectively suppressed.
[0124] The binder is not particularly limited. Known insulating resins and solvents can be used as the binder. The binder preferably contains a thermoplastic component (thermoplastic compound) or a curable component, and more preferably contains a curable component. Examples of the curable component include a photocurable component and a thermosetting component. The photocurable component preferably contains a photocurable compound and a photopolymerization initiator. The thermosetting component preferably contains a thermosetting compound and a thermosetting agent.
[0125] Examples of the binder include vinyl resins, thermoplastic resins, curable resins, thermoplastic block copolymers, elastomers, solvents, etc. The binders may be used alone or in combination of two or more.
[0126] Examples of the vinyl resin include vinyl acetate resin, acrylic resin, and styrene resin. Examples of the thermoplastic resin include polyolefin resin, ethylene-vinyl acetate copolymer, and polyamide resin. Examples of the curable resin include epoxy resin, urethane resin, polyimide resin, and unsaturated polyester resin. The curable resin may be a room temperature curable resin, a thermosetting resin, a photocurable resin, or a moisture curable resin. The curable resin may be used in combination with a curing agent. Examples of the thermoplastic block copolymer include styrene-butadiene-styrene block copolymer, styrene-isoprene-styrene block copolymer, hydrogenated product of styrene-butadiene-styrene block copolymer, and hydrogenated product of styrene-isoprene-styrene block copolymer. Examples of the elastomer include styrene-butadiene copolymer rubber, and acrylonitrile-styrene block copolymer rubber.
[0127] Examples of the solvent include water and organic solvents. Organic solvents are preferred because they can be easily removed. Examples of the organic solvent include alcohol compounds such as ethanol, ketone compounds such as acetone, methyl ethyl ketone, and cyclohexanone, aromatic hydrocarbon compounds such as toluene, xylene, and tetramethylbenzene, glycol ether compounds such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and tripropylene glycol monomethyl ether, ester compounds such as ethyl acetate, butyl acetate, butyl lactate, cellosolve acetate, butyl cellosolve acetate, carbitol acetate, butyl carbitol acetate, propylene glycol monomethyl ether acetate, dipropylene glycol monomethyl ether acetate, and propylene carbonate, aliphatic hydrocarbon compounds such as octane and decane, and petroleum-based solvents such as petroleum ether and naphtha.
[0128] In addition to the conductive particles and the binder, the conductive material may contain various additives such as, for example, a filler, an extender, a softener, a plasticizer, a polymerization catalyst, a curing catalyst, a colorant, an antioxidant, a heat stabilizer, a light stabilizer, an ultraviolet absorber, a lubricant, an antistatic agent, and a flame retardant.
[0129] The method for dispersing the conductive particles in the binder can be a conventionally known dispersion method, and is not particularly limited. Examples of the method for dispersing the conductive particles in the binder include the following methods. A method in which the conductive particles are added to the binder and then kneaded and dispersed with a planetary mixer or the like. A method in which the conductive particles are uniformly dispersed in water or an organic solvent using a homogenizer or the like, then added to the binder, and then kneaded and dispersed with a planetary mixer or the like. A method in which the binder is diluted with water or an organic solvent, then the conductive particles are added, and then kneaded and dispersed with a planetary mixer or the like.
[0130] The viscosity (η25) of the conductive material at 25°C is preferably 30 Pa·s or more, more preferably 50 Pa·s or more, and preferably 400 Pa·s or less, more preferably 300 Pa·s or less. When the viscosity of the conductive material at 25°C is equal to or more than the lower limit and equal to or less than the upper limit, the conductive material can be applied more uniformly to the connection target components, and the occurrence of connection failures can be more effectively suppressed. The viscosity (η25) can be appropriately adjusted by the types and amounts of the blended components.
[0131] The viscosity (η25) can be measured, for example, using an E-type viscometer ("TVE22L" manufactured by Toki Sangyo Co., Ltd.) under conditions of 25° C. and 5 rpm.
[0132] The conductive material can be used as a conductive paste, a conductive film, or the like. When the conductive material is a conductive film, a film not containing conductive particles may be laminated on a conductive film containing conductive particles. The conductive paste is preferably an anisotropic conductive paste. The conductive film is preferably an anisotropic conductive film.
[0133] In 100% by weight of the conductive material, the content of the binder is preferably 10% by weight or more, more preferably 30% by weight or more, even more preferably 50% by weight or more, particularly preferably 70% by weight or more, and is preferably 99.99% by weight or less, more preferably 99.9% by weight or less. When the content of the binder is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged on the connection target member, and the occurrence of connection failure can be more effectively suppressed.
[0134] In 100% by weight of the conductive material, the content of the conductive particles is preferably 0.01% by weight or more, more preferably 0.1% by weight or more, and is preferably 80% by weight or less, more preferably 60% by weight or less, even more preferably 40% by weight or less, particularly preferably 20% by weight or less, and most preferably 10% by weight or less. When the content of the conductive particles is equal to or more than the lower limit and equal to or less than the upper limit, the conductive particles are efficiently arranged on the connection target member, and the occurrence of connection failure can be more effectively suppressed.
[0135] (Connection structure) The connection structure according to the present invention comprises a first connection target member having a first electrode on its surface, a second connection target member having a second electrode on its surface, and a connection part having an insulating member and conductive particles. In the connection structure according to the present invention, the conductive particles are the conductive particles described above. In the connection structure according to the present invention, the first electrode and the second electrode are electrically connected by the conductive particles.
[0136] The connection portion is preferably a socket portion formed by a socket, or a connector portion formed by a connector.
[0137] FIG. 4 is a front cross-sectional view that typically shows a connection structure using conductive particles according to the first embodiment of the present invention.
[0138] The connection structure 51 shown in FIG. 4 includes a first connection target member 52, a second connection target member 53, and a connection portion 54. The first connection target member 52 has a plurality of first electrodes 52a on its surface (upper surface). The second connection target member 53 has a plurality of second electrodes 53a on its surface (lower surface). The connection portion 54 has conductive particles 1, an insulating member 31, a solder paste portion 32, an electrode 33, and a solder ball 34. The connection portion 54 is a socket portion. The insulating member 31 has a through hole 31a penetrating the upper surface and the lower surface.
[0139] A solder ball 34 is disposed on the first electrode 52a. An insulating member 31 is disposed on the solder ball 34. An electrode 33 is disposed on the insulating member 31. A solder paste portion 32 is disposed on the electrode 33. Conductive particles 1 are disposed on the solder paste portion 32. A second electrode 53a is disposed on the conductive particles 1. A conductive paste for via filling is disposed inside the through hole 31a.
[0140] One first electrode 52a is electrically connected to one solder ball 34, one electrode 33, one solder paste portion 32, one conductive particle 1, and one second electrode 53a. Therefore, in the connection structure 51, the first electrode 52a and the second electrode 53a are electrically connected by the conductive particle 1.
[0141] 4, the conductive particles 1 are shown in a schematic diagram for convenience of illustration. Instead of the conductive particles 1, other conductive particles such as conductive particles 11 and 21 may be used.
[0142] In the connection structure according to the present invention, the conductive particles described above are used, so that even if the conductive particles are repeatedly compressed, the occurrence of cracks in the conductive portion can be effectively suppressed. Therefore, it can be used in place of a metal terminal (metal pin), and can accommodate further narrowing of the pitch. In addition, the conductive particles according to the present invention can make the conductive portion less likely to crack even if it is repeatedly compressed, so that the occurrence of connection failures when connecting a CPU, etc. can be effectively suppressed.
[0143] Examples of the material of the insulating member include ceramics and resins. Examples of the resin include fluororesin, phenolic resin, epoxy resin, polyimide resin, etc. Examples of the substrate on which the insulating member is provided include FR-1, FR-2, FR-3, FR-4, FR-5, XPC, CEM-1, CEM-3, glass polyimide substrate, glass PPO substrate, and BT substrate.
[0144] The first and second connection target members are not particularly limited. The first connection target member may be a motherboard, etc. The second connection target member may be a semiconductor chip, an IC package, a CPU, etc.
[0145] Examples of the electrodes provided on the first and second connection target members include metal electrodes such as gold electrodes, nickel electrodes, tin electrodes, aluminum electrodes, copper electrodes, molybdenum electrodes, silver electrodes, SUS electrodes, and tungsten electrodes. When the electrodes are aluminum electrodes, they may be made of aluminum alone, or may be electrodes in which an aluminum layer is laminated on the surface of a metal oxide layer. Examples of materials for the metal oxide layer include indium oxide doped with a trivalent metal element and zinc oxide doped with a trivalent metal element. Examples of the trivalent metal element include Sn, Al, and Ga.
[0146] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0147] The following base particles were prepared.
[0148] Base particle (S1): Divinylbenzene copolymer resin particle (Sekisui Chemical Co., Ltd. "Micropearl GS-L400", particle diameter 400 μm Base particle (S2): Divinylbenzene copolymer resin particle (Sekisui Chemical Co., Ltd. "Micropearl SP-230", particle diameter 30 μm Base particle (S3): Divinylbenzene copolymer resin particle (Sekisui Chemical Co., Ltd. "Micropearl GS-L600", particle diameter 600 μm Base particle (S4): Divinylbenzene copolymer resin particles (Sekisui Chemical Co., Ltd. "Micropearl GS-L1000", particle diameter 1000 μm Base particle (S5): Acrylic copolymer resin particle (Sekisui Chemical Co., Ltd. "Micropearl EZ4P-L400", particle diameter 400 μm Base particle (S6): Divinylbenzene copolymer resin particle (Sekisui Chemical Co., Ltd. "Micropearl ELP-L400", particle diameter 400 μm
[0149] Example 1 Preparation of conductive particles 1: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 1 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0150] Example 2 Preparation of conductive particles 2: The base particle (S1) was electrolessly copper plated to form a copper plating layer with an average thickness of 0.3 μm on the surface of the base particle (S1), and then electrolytic copper plating was performed until the average thickness of the entire copper plating layer reached 4.0 μm, forming a copper plating layer (first conductive part) with an average thickness of 4.0 μm. Next, electrolytic gold plating was performed on the outer surface of the copper plating layer to form a gold plating layer (second conductive part) with an average thickness of 0.5 μm. In this way, a conductive particle 2 having a two-layer laminate structure of a copper plating layer and a gold plating layer was obtained as the conductive part.
[0151] Example 3 Preparation of conductive particles 3: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, an electrolytic plating solution containing copper and beryllium was used to electrolytically plate the outer surface of the nickel plating layer to form a copper-beryllium alloy plating layer (copper:beryllium=98% by weight:2% by weight) having an average thickness of 4.0 μm (second conductive part). In this way, conductive particles 3 having a two-layer laminate structure of a nickel plating layer and a copper-beryllium alloy plating layer were obtained as the conductive part.
[0152] Example 4 Preparation of conductive particles 4: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, an electrolytic plating solution containing copper and zinc was used to electrolytically plate the outer surface of the nickel plating layer to form a copper-zinc alloy plating layer (copper:zinc=70% by weight:30% by weight) having an average thickness of 4.0 μm (second conductive part). In this way, conductive particles 4 having a two-layer laminate structure of a nickel plating layer and a copper-zinc alloy plating layer were obtained as the conductive part.
[0153] Example 5 Preparation of conductive particles 5: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive portion) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, an electrolytic plating solution containing copper and tin was used to electrolytically plate the outer surface of the nickel plating layer to form a copper-tin alloy plating layer (copper:tin=98% by weight:2% by weight) having an average thickness of 4.0 μm (second conductive portion). In this way, conductive particles 5 having a two-layer laminate structure of a nickel plating layer and a copper-tin alloy plating layer were obtained as the conductive portion.
[0154] Example 6 Preparation of conductive particles 6: The base particle (S1) was electroless nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytic copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytic nickel plated to form a nickel plating layer (third conductive part) having an average thickness of 0.5 μm. Next, the outer surface of the nickel plating layer was electrolytic gold plated to form a gold plating layer (fourth conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 6 having a four-layer laminate structure of a nickel plating layer, a copper plating layer, a nickel plating layer, and a gold plating layer was obtained as the conductive part.
[0155] Example 7 Preparation of conductive particles 7: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically palladium plated to form a palladium plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, conductive particle 7 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a palladium plating layer was obtained as the conductive part.
[0156] Example 8 Preparation of conductive particles 8: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically silver plated to form a silver plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 8 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a silver plating layer was obtained as the conductive part.
[0157] Example 9 Preparation of conductive particles 9: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically ruthenium plated to form a ruthenium plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, conductive particles 9 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a ruthenium plating layer as the conductive part were obtained.
[0158] Example 10 Preparation of conductive particles 10: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically rhodium plated to form a rhodium plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 10 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a rhodium plating layer was obtained as the conductive part.
[0159] Example 11 Preparation of conductive particles 11: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically iridium plated to form an iridium plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 11 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and an iridium plating layer was obtained as the conductive part.
[0160] Example 12 Preparation of conductive particles 12: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, using an electrolytic plating solution containing gold and cobalt, the outer surface of the copper plating layer was electrolytically gold-cobalt alloy plated to form a gold-cobalt alloy plating layer (gold:cobalt=98% by weight:2% by weight) having an average thickness of 0.5 μm (third conductive part). In this way, a conductive particle 12 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold-cobalt alloy plating layer was obtained as the conductive part.
[0161] Example 13 Preparation of conductive particles 13: Except for having nickel particles (average particle size: 400 nm) adsorbed in advance as protrusion core materials onto the base particle (S1), conductive particles 13 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer were obtained in the same manner as in Example 1. The conductive particles 13 have a plurality of protrusions on the outer surface of the conductive portion.
[0162] Example 14 Preparation of conductive particles 14: Except for having titanium oxide particles (average particle diameter: 400 nm) adsorbed in advance onto the base particle (S1) as a protrusion core material, conductive particles 14 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer were obtained in the same manner as in Example 1. The conductive particles 14 have a plurality of protrusions on the outer surface of the conductive portion.
[0163] Example 15 Preparation of conductive particles 15: The base particle (S2) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.1 μm on the surface of the base particle (S2). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 0.6 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.03 μm. In this way, a conductive particle 15 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0164] (Example 16) Preparation of conductive particles 16: The base particle (S3) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S3). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 6.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 16 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0165] (Example 17) Preparation of conductive particles 17: The base particle (S4) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.5 μm on the surface of the base particle (S4). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 10.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 1.0 μm. In this way, a conductive particle 17 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0166] (Example 18) Preparation of conductive particles 18: The base particle (S2) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S2). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 5.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.03 μm. In this way, a conductive particle 18 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0167] (Example 19) Preparation of conductive particles 19: The base particle (S4) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.5 μm on the surface of the base particle (S4). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 2.5 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 19 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0168] (Example 20) Preparation of conductive particles 20: The base particle (S5) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S5). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 20 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0169] Example 21 Preparation of conductive particles 21: The base particle (S6) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 0.3 μm on the surface of the base particle (S6). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 4.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 21 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0170] Example 22 Preparation of conductive particles 22: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 2.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 2.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 22 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0171] Example 23 Preparation of conductive particles 23: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 2.8 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 1.5 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 23 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0172] (Example 24) Preparation of conductive particles 24: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 3.3 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically copper plated to form a copper plating layer (second conductive part) having an average thickness of 1.0 μm. Next, the outer surface of the copper plating layer was electrolytically gold plated to form a gold plating layer (third conductive part) having an average thickness of 0.5 μm. In this way, a conductive particle 24 having a three-layer laminate structure of a nickel plating layer, a copper plating layer, and a gold plating layer was obtained as the conductive part.
[0173] Comparative Example 1 Preparation of conductive particles X1: The base particle (S1) was electrolessly nickel plated to form a nickel plating layer (first conductive part) having an average thickness of 5.0 μm on the surface of the base particle (S1). Next, the outer surface of the nickel plating layer was electrolytically gold plated to form a gold plating layer (second conductive part) having an average thickness of 0.5 μm. In this way, conductive particles X1 having a two-layer laminate structure of a nickel plating layer and a gold plating layer as the conductive part were obtained.
[0174] (evaluation) (1) Thickness of the conductive part of the conductive particle The obtained conductive particles were added to Kulzer's "Technovit 4000" so that the content was 30% by weight, and dispersed to prepare an embedding resin for testing. A cross section of the conductive particles was cut out using an ion milling device (Hitachi High-Technologies Corporation's "IM4000") so as to pass through the center of the conductive particles dispersed in the embedding resin for testing.
[0175] Then, using a field emission transmission electron microscope (FE-TEM) (JEM-ARM200F manufactured by JEOL Ltd.), the image magnification was set to 50,000 times, 10 conductive particles were randomly selected, and the conductive part of each conductive particle was observed. The thickness of the conductive part of each conductive particle was measured, and the arithmetic average was calculated to obtain the thickness of the conductive part.
[0176] (2) Particle size of conductive particles The particle size of the obtained conductive particles was calculated using a particle size distribution measuring device (Multisizer 4 manufactured by Beckman Coulter, Inc.) Specifically, the particle sizes of about 100,000 conductive particles were measured and the average value was calculated.
[0177] In addition, from the obtained results, the ratio of the particle diameter of the conductive particles to the thickness of the conductive portion (particle diameter of conductive particles / thickness of conductive portion) was calculated.
[0178] (3) Resistance value of conductive particles For the obtained conductive particles, the resistance value (R1) of the conductive particles was measured after loading and unloading once until the conductive particles were compressed by 20%, and the resistance value (R20) of the conductive particles was measured after loading and unloading until the conductive particles were compressed by 20% 20 times.
[0179] The resistance value (R1) and the resistance value (R20) were measured as follows.
[0180] The following compression test was performed using a micro-compression tester ("ENT-NEXUS" manufactured by Elionix). Conductive particles were scattered on a Pt-coated glass plate, and a cylindrical (diameter 500 μm, made of BeCu / Au on stainless steel) smooth indenter end face was used to apply a load at 25°C in the direction of the center of the conductive particles until the conductive particles were deformed by 20%. The process of unloading the load was counted as one cycle, and a total of 20 cycles of compression tests were performed. After 20% compression deformation in the first cycle, the conduction resistance was calculated from the voltage and current values between the indenter and the substrate measured in the 20% compression deformation state, and this was taken as the resistance value (R1). After 20% compression deformation in the 20th cycle, the conduction resistance was calculated in the same manner in the 20% compression deformation state, and this was taken as the resistance value (R20).
[0181] From the obtained results, the ratio (R20 / R1) of the resistance value (R20) to the resistance value (R1) was calculated.
[0182] (4) Compression test of conductive particles For the obtained conductive particles, the presence or absence of a bend was confirmed in the compression displacement-compression load curve in a compression test (20% compression test or 30% compression test) in which loading and unloading were repeated 20 times until the conductive particles were compressed by 20% or 30%.
[0183] The presence or absence of the bent portion was confirmed as follows.
[0184] The following compression test was performed using a micro-compression tester (Shimadzu Corporation's "Micro Autograph MST-I"). Conductive particles were scattered on a Pt-coated glass plate, and a cylindrical (diameter 500 μm, made of diamond) smooth indenter end face was used to apply a load at 25° C. in the direction of the center of the conductive particles at a compression speed of 0.3 mN / sec until the conductive particles were compressed by 20% or 30% and then unloaded, which was defined as one cycle. A total of 20 cycles of compression tests were performed. The compression displacement (μm) and compression load (mN) during this period were measured, and the presence or absence of a bend was confirmed in the compression displacement curve showing the relationship between the compression displacement (X-axis) and the compression load (Y-axis).
[0185] (5) Cracks in the conductive part of the conductive particles Twenty conductive particles were prepared after the above (4) compression test (20% compression test or 30% compression test). The prepared conductive particles were observed using a scanning electron microscope (SEM) to confirm whether cracks had occurred in the conductive part of the conductive particle. Cracks in the conductive part of the conductive particle were judged under the following conditions.
[0186] [Criteria for determining cracks in the conductive part of conductive particles] XXX: No cracks have occurred in the conductive part of the conductive particles 〇〇: Cracks with a length of less than 30% of the particle diameter have occurred along the surface of the conductive part of the conductive particle. ○: A crack with a length of 30% or more but less than 50% of the particle diameter has occurred along the surface of the conductive part of the conductive particle. ×: A crack with a length of 50% or more of the particle diameter occurs along the surface of the conductive part of the conductive particle.
[0187] (6) Connection failure in connection structure 1 Using the obtained conductive particles, a connection structure (a connection structure having the structure shown in FIG. 4) was produced as follows.
[0188] A BGA substrate was prepared in which solder balls and metal pads (hereafter referred to as LANDs) were electrically connected via through-holes. In this BGA substrate, conductive paste for via-filling was placed inside the through-holes.
[0189] The BGA substrate was assembled into a package receiving unit equipped with a package fixing unit for fixing an IC package. Then, a solder paste was applied onto the LAND on the upper surface of the BGA substrate using a dispenser. The obtained conductive particles were placed onto the applied solder paste using a ball mounter. Then, the substrate was heated in a reflow furnace at 280°C for 3 minutes in a nitrogen atmosphere. In this way, an IC socket was obtained in which the LAND and the conductive particles were joined via solder, and the lower part of the BGA substrate assembled into the package receiving unit was joined via solder to an electric circuit board (motherboard).
[0190] To mount an IC package (CPU) on the obtained IC socket, the lever on the package fixing unit was raised to open the pressure cover, and the IC socket was set on the package receiving unit so that the LAND part at the bottom of the IC package came into contact with the conductive particles arranged on the BGA board. With the pressure cover lowered, the lever was pushed down so that the pressure cover pressed down on the IC package from above, applying a vertical load to the IC package toward the contacts, and a connection structure was obtained.
[0191] The resulting connection structure was observed using a scanning electron microscope (SEM) to check whether or not a connection defect had occurred. Connection defect 1 was judged according to the following criteria.
[0192] [Criteria for determining connection failure 1] ○: No connection problems have occurred ×: A connection error has occurred.
[0193] (7) Connection failure in connection structure 2 Two printed circuit boards (10 mm long x 10 mm wide) were prepared as the first and second connection target members. In the above printed circuit boards, 121 through electrodes were formed on the surface at a pitch of 0.8 mm. Solder paste ("M705-GRN360-K2-V" manufactured by Senju Metal Industry Co., Ltd.) was applied to the LANDs of the first connection target member. The obtained conductive particles were placed on all the LANDs to which the solder paste was applied, and the conductive particles were mounted on the LANDs by heating them in a reflow furnace at 250°C for 30 seconds in a nitrogen atmosphere.
[0194] Next, a ball mounter ("CB-505" manufactured by Athlete FA) was used to press the LAND of the second connection target member against the conductive particles, and a vertical load of 30 g was applied to one conductive particle to compress and deform the conductive particle. The ball mounter was then decompressed, and after one minute had passed, the ball mounter was used again to compress and deform the conductive particle in the same manner to obtain a connection structure. This process constitutes one cycle, and a total of 20 cycles of compression tests were performed. After one cycle and after 20 cycles, the conduction resistance of each electrode was measured using a resistance measuring device (RM3542A manufactured by Hioki E.E.C.), and the resistance value after 20 cycles (Q20) and the resistance value after one cycle (Q1) were measured. From the results obtained, the ratio (Q20 / Q1) of the resistance value (Q20) to the resistance value (Q1) was calculated for each electrode, the average was calculated, and the results were evaluated according to the following criteria. In addition, since the obtained connection structure has a through electrode formed therein, the resistance value can be measured even if one LAND is broken.
[0195] [Criteria for determining connection failure 2] ○○○: The average of the above ratio (Q20 / Q1) is 1.0 or more and less than 1.15, and there is no electrode with the above ratio (Q20 / Q1) of 1.5 or more. XX: The average of the above ratio (Q20 / Q1) is 1.15 or more and less than 1.3, and there is no electrode with the above ratio (Q20 / Q1) of 1.5 or more. ○: The average of the ratio (Q20 / Q1) is 1.3 or more and less than 1.5, and there is no electrode with the ratio (Q20 / Q1) of 1.5 or more. ×: At least one of the following applies: "The average of the above ratio (Q20 / Q1) is 1.5 or more" and "An electrode having the above ratio (Q20 / Q1) of 1.5 or more is present."
[0196] The results are shown in Tables 1 to 4 below.
[0197] [Table 1]
[0198] [Table 2]
[0199] [Table 3]
[0200] [Table 4]
[0201] [Table 5] [Explanation of symbols]
[0202] 1...Conductive particles 2...Base material particles 3...Conductive part 11...Conductive particles 11a...Protrusion 12...Conductive part 12a...Protrusion 13…core substance 21...Conductive particles 21a...Protrusion 22...Conductive part 22a...protrusion 22A…First conductive part 22Aa…Protrusion 22B...Second conductive part 22Ba…Protrusion 31...Insulating material 31a…Through hole 32...Solder paste section 33...Electrode 34…Solder ball 35...Metal terminal (metal pin) 51,101…Connection structure 52...First connection target member 52a...first electrode 53...Second connecting member 53a...second electrode 54,104…Connection
Claims
1. A conductive particle including a base particle and a conductive portion disposed on a surface of the base particle, The conductive particles have a particle diameter of 30 μm or more, Conductive particles, wherein the ratio of the resistance value of the conductive particle after the conductive particle is repeatedly loaded and unloaded until it is compressed by 20% 20 times to the resistance value of the conductive particle after the conductive particle is loaded and unloaded once until it is compressed by 20% is 1.5 or less.
2. A conductive particle including a base particle and a conductive portion disposed on a surface of the base particle, The conductive particles have a particle diameter of 30 μm or more, Conductive particles, which have no bends in a compression displacement-compression load curve in a compression test in which loading and unloading are repeated 20 times until the conductive particles are compressed and deformed by 20%.
3. 3. The conductive particle according to claim 2, wherein a compression displacement-compression load curve in a compression test in which loading and unloading are repeated 20 times until the conductive particle is compressed by 30% has no bend.
4. A conductive particle including a base particle and a conductive portion disposed on a surface of the base particle, The conductive particles have a particle diameter of 30 μm or more, Conductive particles used to obtain sockets or connectors.
5. The conductive particle according to any one of claims 1 to 4, wherein the material of the conductive portion comprises a ductile metal.
6. The conductive portion has a laminated structure of two or more layers, The conductive particle according to any one of claims 1 to 5, wherein a layer other than the outer surface of the conductive portion comprises a layer containing a ductile metal.
7. The conductive particle according to claim 6 , wherein the material of the outer surface of the conductive portion is gold, silver, copper, tin, zinc, nickel, beryllium, cobalt, palladium, platinum, rhodium, ruthenium, iridium, or an alloy thereof.
8. The conductive particle according to claim 6 or 7, wherein the layer containing the ductile metal has a thickness of 0.6 μm or more.
9. The conductive particle according to any one of claims 1 to 7, wherein the conductive portion has a thickness of 0.3 µm or more and 20 µm or less.
10. The conductive particle according to any one of claims 1 to 9, wherein the conductive portion has a thickness of 0.6 µm or more and 20 µm or less.
11. The conductive particle according to any one of claims 1 to 10, wherein a ratio of a particle diameter of the conductive particle to a thickness of the conductive portion is 5 or more and 300 or less.
12. The conductive particle according to any one of claims 1 to 11, having a plurality of protrusions on the outer surface of the conductive portion.
13. The conductive particles according to any one of claims 1 to 12, wherein a load of 50 N or less is required to compress and deform the conductive particles by 20%.
14. The conductive particles according to any one of claims 1 to 13, wherein a load necessary for compressing and deforming the conductive particles by 30% is 100 N or less.
15. a first connection target member having a first electrode on a surface thereof; a second connection target member having a second electrode on a surface thereof; a connection portion having an insulating member and conductive particles; The conductive particles are the conductive particles according to any one of claims 1 to 14, A connection structure, wherein the first electrode and the second electrode are electrically connected by the conductive particles.
Citation Information
Patent Citations
Ic socket
JP2001237039A
Conductive particle, anisotropic conductive material, and connection structure
JP2011040189A
Conductive particle with insulating particles, anisotropic conductive material, and connection structure
JP2011060502A
Socket for electronic components and its manufacturing method as well as mounting structure using the socket for the electronic components
JP2003297507A